THE ROLE OF MODERN TECHNOLOGIES IN ENHANCING BANKS PROFITABILITY - Ahmed Jasim Mohammed; Ahmed Abbas Hussein; Mohsin N. AL-Maliki (American Journals, 2023)
Purpose: This study aims to explore the extent to which modern technologies contribute, both as independent and dependent variables, towards enhancing the profitability of banks. Design/Methodology/Approach: In order to address the research problem, find solutions, achieve its objectives, and test its hypotheses, several branches of Rafidain and Rashid banks operating in Misan Province were selected. A purposeful sample of 25 employees from these banks at various managerial levels was chosen. Data collection was conducted using a questionnaire, and the collected data were processed and the study’s hypotheses were tested using various statistical methods, including SPSS and Excel. Results and Recommendations: The research results indicate a significant impact relationship between modern technologies as an independent variable and bank profitability as a dependent variable at a significance level of 0.05. The research recommends giving greater attention to and incorporating modern technologies into banking operations as they are considered an important means of increasing bank profitability, enhancing competitiveness, and securing a larger market share.
Keywords: Modern Technologies; Banks Profitability; Iraqi Banks.